Study of Microstructure 304L Austenitic Stainless Steel Weld Deposited by GTAW for Root Pass and SMAW for Filler Passes - Randhawa, Harsimranjit Singh; Kumar, Sunil (Asian Journal of Engineering and Applied Technology, 2018)
In the present experimentation, a 10mm thick austenitic stainless steel plate type 304L is welded using single V-joint configuration and approaching the joint from one side. Back purging has been employed to protect the rear side of the root pass weld metal against oxidation. The root pass has been deposited by gas tungsten arc welding (GTAW) process. The filler passes are deposited by shielding metal arc welding (SMAW) process at 90A and 120A welding currents giving heat inputs of the order of 0.679 and 0.933 kJ/mm respectively while the speed of weld deposition was kept practically constant. The results of experimentation show that the micro-hardness of weld metal and heat affected zone (HAZ) of weldments produced at lower heat input is higher whereas impact toughness value of weld metal and HAZ is lower than that of joints produced at higher heat input. The microstructure of weld metal and heat affected zone developed at lower weld heat input has been observed finer in comparison to that resulted at higher heat input. This has primarily happened due to a higher rate of cooling at low heat input.